An automated method to evaluate the enzyme kinetics of β-glucosidases - Klimeš, Pavel; Mazura, Pavel; Turek, Dušan; Brzobohatý, Břetislav (Protein science, 2017)
Enzyme kinetic measurements are important for the characterization and engineering of biocatalysts, with applications in a wide range of research fields. The measurement of initial reaction velocity is usually slow and laborious, which motivated us to explore the possibilities for automating this process. Our model enzyme is the maize β-glucosidase Zm-p60.1. Zm-p60.1 plays a significant role in plant growth and development by regulating levels of the active plant hormone cytokinin. Zm-p60.1 belongs to a wide group of hydrolytic enzymes. Members of this group hydrolyze several different types of glucosides, releasing glucose as a secondary product. Enzyme kinetic measurements using artificial substrates are well established, but burdensome and time-consuming. Thus, they are a suitable target for process automation. Simple optical methods for enzyme kinetic measurements using natural substrates are often impossible given the optical properties of the enzymatic reaction products. However, we have developed an automated method based on glucose detection, as glucose is released from all substrates of glucosidase reactions. The presented method can obtain 24 data points from up to 15 substrate concentrations to precisely describe the enzyme kinetics. The combination of an automated liquid handling process with assays that have been optimized for measuring the initial hydrolysis velocity of β-glucosidases yields two distinct methods that are faster, cheaper, and more accurate than the established protocols.
Keywords: rostlinné proteiny; kinetika; Automation; glucose; lab automation; katalýza; automatizace; Catalysis; Zea mays; beta-glukosidasa; enzyme kinetics; β-glucosidase; beta-Glucosidase; glycoside hydrolases; fluorescence; Plant Proteins; Kinetics; kukuřice setá